Multisensory Physical Computing for the Blind and Visually Impaired - Potluri, Venkatesh; Mankoff, Jennifer; Devine, James; Hodges, Steve (CHI 2021 - Rethinking the Senses: A Workshop on Multisensory Embodied Experiences and Disability Interactions, 2021)
Physical computing is a powerful technique that motivates engagement with technology, supports learning, and allows users to build useful interactive devices. Here we propose new approaches hardware design and programming environment design to make physical computing more accessible to people who are blind or visually impaired.